Self-disciplinary time-restricted smartphone addiction management system using (android) mobile technology (2018)
The values of smartphone devices have increased tremendously over last few years, especially with the development of mobile applications which have been beneficial. According to Google, there are over a billion active users of mobile applications deployed on Android Playstore as at 2015. This means that there are over a billion users who actually spend time on their smartphones. However, despite the tremendous advantages of smartphones and the applications that can be installed on them, there are negative consequences that can come from spending countless number of hours on a smartphone and, applications that help in curbing these addictions are really scarce. There still exists a large inefficiency in the current systems that help to curb or manage smartphone addictions. In view of the above, this study sought to present a time-restricted smartphone addiction system that is effective, efficient and relevant. This study explored the use of mobile technology in the design and development of the system (the application), which enables a user to select the applications he or she wants to lock within a specified period of time and at the same time gives the user an overall view of how often he or she uses the applications installed on the device.